Management challenges for best practices of the Kangaroo Method in the Neonatal ICU - Laura Johanson da Silva; Joséte Luzia Leite; Thiago Privado da Silva; Ítalo Rodolfo Silva; Pâmela Pereira Mourão; Tainá Martins Gomes
ABSTRACT Objective: To understand the conditions that influence the adherence and application of best practices by nurses in the context of the Nursing care management in the Kangaroo Mother Care in the Neonatal ICU. Method: Study of qualitative approach, whose theoretical and methodological frameworks were Symbolic Interactionism and Grounded Theory, respectively. We used the in-depth interview with 8 nurses from the Neonatal ICU of a public maternity hospital in the city of Rio de Janeiro. Results: The conditions involved in adhering to the best practices of humanization in the Neonatal ICU are related mainly to human resources, interaction among professionals, work processes and leadership strategies; and care management. Conclusion: Professional and institutional challenges have been identified that need to be addressed to improve adherence and implementation of the Kangaroo Mother Care best practices.